como eu faço essa conta de equação de 1° grau; -3x=27
Soluções para a tarefa
Respondido por
1
-3x = 27
x = 27 ÷ -3
x = -9
obs= -3 vezes - 9 = +27
x = 27 ÷ -3
x = -9
obs= -3 vezes - 9 = +27
LucasRicarte:
obrigado ^^
É simples.
3x - 27 = 0
x = 27/3
x = 9
É isso,
espero ter ajudado.
Respondido por
2
Olá Lucas !
![- 3x = 27 \\ 3x = - 27 \\ x = - \frac{27}{3} \\ x = - 9 - 3x = 27 \\ 3x = - 27 \\ x = - \frac{27}{3} \\ x = - 9](https://tex.z-dn.net/?f=-+3x+%3D+27++%5C%5C+3x+%3D+-+27+%5C%5C+x+%3D+-++%5Cfrac%7B27%7D%7B3%7D++%5C%5C+x+%3D+-+9)
Tenha bons estudos !
Tenha bons estudos !
Perguntas interessantes